Renewable Cyclopentanol From Catalytic Hydrogenation-Rearrangement of Biomass Furfural Over Ruthenium-Molybdenum Bimetallic Catalysts - Meng, Shihang; Weng, Yujing; Wang, Xiaolong; Yin, Hongxing; Wang, Zhenfei; Sun, Qi; Fan, Maohong; Zhang, Yulong (Frontiers in Bioengineering and Biotechnology, 2020)
Biomass furfural like compounds are chemicals that cannot be extracted from fossil materials, through which a large number of fine chemicals and fuel additives can be opened up, but one big efficiency problem during the transformation is the accumulation of oligomers. Here, we propose a novel and efficient Ru-Mo bimetallic catalyst for selective hydrogenation-rearrangement of furfural like compounds. The result showed that an unprecedented rearrangement product selectivity of 89.1% to cyclopentanol was achieved under an optimized reaction condition over a 1%Ru-2.5%Mo/CNT catalyst reduced at 600 ℃. Subsequent characterization suggested that the catalyst presented the weak acidity and strong hydrogenation activity for the reaction, which not ensures the smooth hydrogenation-rearrangement reaction but also inhibits the accumulation of furan polymers. These findings provide a convenient strategy to tune the catalytic performance of Mo-based catalysts by controlling the reduction and carburization conditions, which appear to be versatile for the rearrangement of furans and similar compounds.